Urban Transportation Innovation: Implementation of the “Biskita Trans Pakuan” Bus Transportation Policy as an Effort to Improve Mass Transportation in Bogor City 2021-2022 - Nebula Sangga Buana Susanto Putri, Bintang Avroditha; Munandar, Moh. Aris (Universitas Negeri Semarang, 2023)
Massive transportation management is needed to overcome traffic problems that are common in big cities, such as congestion. Bogor itself is famous for its traffic jams as a result of the booming number of city transportation or public transportation, especially in the central area of Bogor. The Central Government together with the Bogor Government presented an urban transportation innovation program in the form of reducing and converting public transportation (angkot) into “BisKita Trans Pakuan Bogor” buses to overcome this traffic jam problem. This study aims to examine how the “BisKita Trans Pakuan” bus transportation policy is implemented. This research focuses on how the Bogor Government implements the “BisKita Trans Pakuan” bus program from planning to public policy evaluation. This study uses a mixed method or mixed method exploratory sequential design which begins with collecting and analyzing data in the form of qualitative, which in the next stage with the collection of quantitative data to strengthen the research results. The main weight of this study is on qualitative data. Sources of data are taken through data collection techniques such as interviews, observation, questionnaires, and documentation. A data validity test was carried out by data triangulation. Data analysis techniques are carried out in several ways, namely data collection, data reduction, data presentation, and conclusion. The results of this study show that the Bogor City Government is utilizing the “BisKita Trans Pakuan” BTS program to reduce congestion by converting urban transportation that crowds the SSA line (one-way system) resulting in traffic jams almost every day.